Exploring the Values of Local Wisdom of the Meukisi Indigenous Community, Papua - Layan, Santy; Malatuny, Yakob Godlif (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
The existence of the indigenous community in Meukisi Village is becoming increasingly concerning, because in recent decades this community has become vulnerable to change. In fact, the values of local wisdom have been deeply rooted and traditional in the lives of their ancestors. The approach in this study is qualitative using the case study method. Meukisi traditional leaders became informants. The researcher used techniques such as in-depth interviews, observation, and documentation studies. Meanwhile, data analysis techniques were carried out through the stages of data reduction, data presentation, conclusion drawing, and verification. The research found that the indigenous people of Meukisi have adopted yau as a guideline for their attitudes and actions. Yau has become a guiding star for the Meukisi indigenous community. The Meukisi indigenous community maintains and preserves yau through guidance and habit formation within the family and policies from indigenous institutions to provide guidance for the younger generation in indigenous activities that take place once a year. It can be concluded that, fundamentally, the existence of local yau wisdom values is dynamic because it adapts to the changing times, as it is able to survive in the face of globalization and is used as a means of strengthening the identity of the Meukisi indigenous community.